2019
DOI: 10.1016/j.xkme.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Acute Kidney Injury in the Critically Ill

Abstract: Rationale & Objective Uric acid is excreted by the kidney and accumulates in acute kidney injury (AKI). Whether higher plasma uric acid level predisposes to AKI or its complications is not known. Study Design Prospective observational cohort study. Setting & Participants 2 independent cohorts of critically ill patients: (1) 208 patients without AKI admitted to the intensive care unit (ICU) at Brigham & Women’s Hospital between October 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…These findings might suggest that targeting SUA levels to normal ranges should be a principal goal to extend patient survival. However, whether this would confer an absolute survival benefit in all patient subgroups remains to be proven from appropriately designed clinical trials [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These findings might suggest that targeting SUA levels to normal ranges should be a principal goal to extend patient survival. However, whether this would confer an absolute survival benefit in all patient subgroups remains to be proven from appropriately designed clinical trials [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bagshaw SM et al concluded that septic AKI is independently associated with higher odds of death and longer duration of hospitalization [12] . A study by Anand Srivastava et al Concluded that plasma uric acid levels upon ICU admission or before RRT initiation are not independently associated with adverse clinical outcomes in critically ill patients [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked increased plasma uric acid and poor prognosis and reported an increased risk for AKI among patients with elevated uric acid (136,138). However, in another study using multivariate analysis, such association was no longer significant (139). Uric acid can cause AKI due to a variety of mechanisms ranging from direct tubular toxicity and crystal induced nephropathy to indirect injury secondary to the release of vasoactive mediators and oxidative stress (136).…”
Section: Rasburicasementioning
confidence: 99%